Stress Induced Right Ventricular Diastolic Dysfunction in Non-severe Chronic Obstructive Pulmonary Disease - the Role of Oxidative Stress and Inflammation - Cherneva, Zheina; Valev, Dinko; Youroukova, Vania; Cherneva, Radostina (Cardiology and Cardiovascular Medicine, 2020)
Background: Oxidative stress and inflammation have been implicated in the pathogenesis of diastolic dysfunction (DD) and are both present in chronic obstructive pulmonary disease (COPD). Our aim was to evaluate the role of 8-isoprostane, prostaglandin E2 and resistin for stress induced right ventricular DD (RVDD) in non-severe COPD. Methods: 104 patients with non-severe COPD (FEV1>50%) and preserved left ventricular ejection fraction >50% underwent cardio-pulmonary exercise testing (CPET). Echocardiography was performed before CPET and 1-2 minutes after peak exercise. Peak E/e’ ratio>6 was a marker for stress RVDD. To measure urine concentration of 8-isoprostanes, prostaglandine-E2 and plasma resistin levels mass spectrometry and ELISA were applied. Results: Patients were divided into two groups: with (82) and without stress RVDD (22). In subjects with and without RVDD the levels of 8-isoprostane were (30.78 vs 30.41μmol/l/cre, p-0.847); prostaglandin E2 - (49.73 vs 62. 19 μmol/l/cre, p-0.014); resistin plasma levels (18.91 vs 5.47ng/ml, p-0.027). Resistin and prostaglandine E2 correlated to stress RV E/e’, but were not independent indices for it. RAVI (cut-off 20.55 ml/m2; sensitivity 86%; specificity 86%), RVWT (cut-off 5.25 mm; sensitivity 100%; specificity 63%) and RV E/A at rest (cut-off 1.05; sensitivity 79.7%; specificity 90.5%) independently predicted stress RV E/e’ with the accuracy of 92%. Conclusions: Patients with stress RVDD demonstrate similar levels of oxidative stress. Prostaglandine E2 may have protective role in RV remodeling, while resistin plasma levels contribute to RVDD pathogenesis. RAVI, RVWT, RV E/A and RV E/e’ ratio at rest may be used as independent predictors for stress RVDD.